Impact of acute sleep restriction on resting ventilation and cytokine levels in normobaric hypoxia, and their association - Louis David; Julianne Touron; Marie-Claire Erkel; Catherine Drogou; Anaïs Pontiggia; Vincent Beauchamps; Carine Malle; Olivier Nespoulous; Ulysse Comte; Alexandra Malgoyre; Fabien Sauvet; Beth A. Beidleman; et al. (European Journal of Applied Physiology, 2026)

Black stains of Lascaux Cave involve different melanin synthesis pathways as shown by Alkaline/H2O2 hydrolysis and UHPLC-ESI/QTOF analysis of pigmented fungal isolates and stains from cave walls - Pierre Vergne; Malik Bahsoun; Marie-Geneviève Dijoux-Franca; Gilles Comte; Jeanne Doré; Maximilien Gonçalves-Martins; Lise Alonso; Isabelle Kerzaon; Patricia Luis; Yvan Moënne-Loccoz; Serge Michalet (International Biodeterioration & Biodegradation, 2025)

Extracellular Vesicles of a Phytobeneficial Bacterium Trigger Distinct Systemic Response in Plant - Timothée Zannis‐Peyrot; Lucas Degusseau; Pierre‐Yves Dugas; Fabiola Bastian; Matthieu Gaucher; Vincent Gaillard; Gilles Comte; Florence Wisniewski‐Dye; Isabelle Kerzaon; Céline Lavire; Ludovic Vial (Environmental Microbiology, 2025)
Bacterial extracellular vesicles (EVs) are lipidic shuttles involved in inter‐species communication, virulence, and host immune modulation. While their roles are increasingly understood in animal‐bacteria interactions, knowledge of phytobacterial EVs remains limited. Recent findings indicate that biotic factors like hydroxycinnamic acids can regulate EV production. Hydroxycinnamic acids, such as ferulic acid, are abundant lignin components in the plant environment, influencing the ecology of numerous phytobacteria. Azospirillum sp. B510, a phytobeneficial bacterium, induces the accumulation of hydroxycinnamic acid derivatives in plants and can metabolise them. This study hypothesised that ferulic acid in the Azospirillum sp. B510 environment would influence EV production and, conversely, that these EVs would impact plant metabolites and defence gene expression. Our results demonstrate that ferulic acid influences the content of EVs released by Azospirillum sp. B510. Furthermore, bacterial EVs impact plant physiology at a systemic level according to their cargo. EVs induce systemic changes in Solanum lycopersicum metabolome, including alterations in hydroxycinnamic acid amide derivatives in roots and steroidal alkaloids in aerial tissues. Bacterial EVs also modulate tomato defence gene expression correlating with observed metabolite accumulation patterns. This research provides evidence of a global effect of bacterial EVs, highlighting the dynamic nature of plant‐bacteria interactions mediated by EVs.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Experimenting marine extent and condition accounts in France - Adrien Comte; Frédéric Quemmerais-Amice; Pierre Scemama; Rémi Mongruel; Clément Surun; Harold Levrel (Marine Policy, 2025)

Trajectory optimization for multi-target Active Debris Removal missions - Laura Medioni; Yvan Gary; Myrtille Monclin; Côme Oosterhof; Gaetan Pierre; Tom Semblanet; Perrine Comte; Kévin Nocentini (Advances in Space Research, 2023)

Correction to: Pesticide resurrection - Charles Mottes; Pierre Sabatier; Olivier Evrard; Nathalie Cottin; Fabien Arnaud; Irina Comte; Christine Piot; Magalie Lesueur-Jannoyer; Eric Lichtfouse; Jérôme Poulenard (Environmental Chemistry Letters, 2023)

Pesticide resurrection - Charles Mottes; Pierre Sabatier; Olivier Evrard; Nathalie Cottin; Fabien Arnaud; Irina Comte; Christine Piot; Magalie Lesueur-Jannoyer; Eric Lichtfouse; Jérôme Poulenard (Environmental Chemistry Letters, 2022)

Spatio-temporal variability of water pollution by chlordecone at the watershed scale: what insights for the management of polluted territories? - Charles Mottes; Landry Deffontaines; Jean Baptiste Charlier; Irina Comte; Pauline Della Rossa; Magalie Lesueur-Jannoyer; Thierry Woignier; Georges Adele; Anne-Lise Tailame; Luc Arnaud; Joanne Plet; Luc Rangon; et al. (Environmental Science and Pollution Research, 2020)

Exploiting rhizosphere microbial cooperation for developing sustainable agriculture strategies - Yoann Besset-Manzoni; Laura Rieusset; Pierre Joly; Gilles Comte; Claire Prigent-Combaret (Environmental Science and Pollution Research, 2018)

Erratum to: Biological Effects in Lung Cells In Vitro of Exhaust Aerosols from a Gasoline Passenger Car With and Without Particle Filter - Christoph Bisig; Sandro Steiner; Pierre Comte; Jan Czerwinski; Andreas Mayer; Alke Petri-Fink; Barbara Rothen-Rutishauser (Emission Control Science and Technology, 2017)

Biological Effects in Lung Cells In Vitro of Exhaust Aerosols from a Gasoline Passenger Car With and Without Particle Filter - Christoph Bisig; Sandro Steiner; Pierre Comte; Jan Czerwinski; Andreas Mayer; Alke Petri-Fink; Barbara Rothen-Rutishauser (Emission Control Science and Technology, 2015)

Watershed-scale assessment of oil palm cultivation impact on water quality and nutrient fluxes: a case study in Sumatra (Indonesia) - Irina Comte; François Colin; Olivier Grünberger; Joann K. Whalen; Rudi Harto Widodo; Jean-Pierre Caliman (Environmental Science and Pollution Research, 2015)

Finite Element Model of Soil Water and Nutrient Transport with Root Uptake: Explicit Geometry and Unstructured Adaptive Meshing - Pierre-Henri Tournier; Frédéric Hecht; Myriam Comte (Transport in Porous Media, 2015)